2023
DOI: 10.1093/jee/toad024
|View full text |Cite
|
Sign up to set email alerts
|

Development and Immature Mortality of the Sawtoothed Grain Beetle (Coleoptera: Silvanidae), on Different Sorghum Fractions and Different Temperatures

Abstract: Developmental ability of Oryzaephilus surinamensis (L.) (Coleoptera: Silvanidae) was examined on six different sorghum milling fractions: Bran, Shorts, Cgrits, Fgrits, Red dogs, Flour, and also on a standard diet of Oat Flakes. For this purpose, a 1-day-old egg was placed in a vial containing 1 g of one of the sorghum fractions and exposed to three temperatures: 25, 30, or 32°C. All vials were checked daily for pupal and adult emergence and mortality of immatures. The developmental time was significantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Sorghum is considered as a highly nutritious grain, rich in polyphenols and flavonoids, while its production has gradually increased during the last decade (Cardoso et al 2017 ). Several studies documented that sorghum can be infested by different insect pests during storage that can cause serious damage and qualitative degradations (Arthur et al 2020 ; Gourgouta et al 2021 ; Lampiri et al 2020 , 2023 ). For instance, Lampiri et al ( 2020 ) reported that larvae of the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae) could develop on different sorghum milling fractions, with sorghum bran being most suitable for development.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum is considered as a highly nutritious grain, rich in polyphenols and flavonoids, while its production has gradually increased during the last decade (Cardoso et al 2017 ). Several studies documented that sorghum can be infested by different insect pests during storage that can cause serious damage and qualitative degradations (Arthur et al 2020 ; Gourgouta et al 2021 ; Lampiri et al 2020 , 2023 ). For instance, Lampiri et al ( 2020 ) reported that larvae of the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae) could develop on different sorghum milling fractions, with sorghum bran being most suitable for development.…”
Section: Introductionmentioning
confidence: 99%